Development of Aa New Time Temperature Indicator for Enzymatic Validation of Pasteurization of Meat Products. Issue 6 (5th May 2015) - Brizio, Ana Paula Dutra Resem; Prentice, Carlos
Abstract This paper presents the development of a new smart time‐temperature indicator (TTI) of pasteurization whose operating principle is based on the complexation reaction between starch and iodine, and the subsequent action of an amylase on this complex causing its discoloration at a rate dependent on time and temperature of the medium. Laboratory simulations and tests in a manufacturing plant evaluated different enzyme concentrations in the TTI prototypes when exposed to pasteurization conditions. The results showed that the color response of the indicators was visually interpreted as adaptive to measurement using appropriate equipment, with satisfactory reliability in all conditions studied. The TTI containing 6.5% amylase was one whose best results were suited for use in validating the cooking of hams. When attached to the primary packaging of the product, this TTI indicated the pasteurization process inexpensively, easily, accurately, and nondestructively.